2012
DOI: 10.1016/j.biortech.2011.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of biocatalysts for enzymatic polymerizations: Possibilities, advantages, applications

Abstract: a b s t r a c tBiotechnology also holds tremendous opportunities for realizing functional polymeric materials. Biocatalytic pathways to polymeric materials are an emerging research area with not only enormous scientific and technological promise, but also a tremendous impact on environmental issues. Many of the enzymatic polymerizations reported proceed in organic solvents. However, enzymes mostly show none of their profound characteristics in organic solvents and can easily denature under industrial condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(95 citation statements)
references
References 72 publications
(80 reference statements)
0
89
0
6
Order By: Relevance
“…There are also frequent disadvantages, however, including difficult enzyme recovery, low product concentration, low productivity due to substrate and/or product inhibition and, hence, high recovery costs [34]. An important route to improving the performance of enzymes in non-natural environments and their ability to work in continuous processes is to immobilize them by either adsorption, covalent attachment or by incorporation in hydrophobic organic-inorganic hybrid materials [35][36][37][38].…”
Section: Biocatalysismentioning
confidence: 99%
“…There are also frequent disadvantages, however, including difficult enzyme recovery, low product concentration, low productivity due to substrate and/or product inhibition and, hence, high recovery costs [34]. An important route to improving the performance of enzymes in non-natural environments and their ability to work in continuous processes is to immobilize them by either adsorption, covalent attachment or by incorporation in hydrophobic organic-inorganic hybrid materials [35][36][37][38].…”
Section: Biocatalysismentioning
confidence: 99%
“…A small pore size can cause diffusion limitation resulting in structural rearrangement of the enzymes and subsequent inactivity. However, for very large pore sizes, enzymes can cluster together and thus lose activity (Miletic et al, 2012).…”
Section: Immobilized Enzyme Supportsmentioning
confidence: 99%
“…Other studies have shown that immobilization can hinder or enhance the enzyme efficacy, depending on the specific enzyme and immobilization support combination [13,14]. Immobilization often restricts folding and unfolding of the enzymes leading to changes in how they respond to differences in pH and temperature compared to free enzymes.…”
Section: Introductionmentioning
confidence: 98%